Formulasi Dan Evaluasi Emulsi Kombinasi Ekstrak Tomat (Lycopersicum Esculentum) Dan Minyak Zaitun (Olea Europaea) Dengan Variasi Span 80 Dan Tween 80 Sebagai Emulgator - Vera Astuti; Ratna Ningsih Dewi Astuti; Cik Ayu (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2020)
Emulsion is a pharmaceutical preparation in the form of a liquid that combines two substances that are notmixed, usually aqueous and oil. Olive oil and tomatoes are efficacious as antihypertensive.The purpose of thisresearch is formulate tomatoes (Lycopersicum esculentum ) extract and olive oil (Olea europaea) becomes O/Wemulsion. O/W emulsion more stable using a combination emulgator as span 80 and tween 80, because it hasbalance between hydrophilic and lipophilic substances so that it can unite all types of solutions. This study wasa experimental.Variation of span 80 and tween 80 concentrations is 3%:5% formula I, 3,36%:5,64% formula II,3,74%:6,26% formula III. After that, it is evaluated at room temperature storage for 28 days, that are pH,viscosity, specific gravity, homogenity, phase separation, emulsion type, color, odor and taste.Based on theresults obtained, both pH, viscosity and specific gravity are decrease. For evaluasion of phase separation, onlyformula I does meet the requirements. Based on evaluation homogenity, emulsion type, color, odorl and taste allformulas meet the requirements during storage28 days. Tomatoes (Lycopersicum esculentum ) extract and oliveoil (Olea europaea) can formulate becomes stable and eligible emulsion. The most optimal formula is formulaIII with concentration 3,74% of span 80 and 6,26% of tween 80.